[Waves Against Sea Cave at Westman Islands] - Streng, Evelyn Fiedler (1975)
Photograph of waves crashing against a sea cave at the Westman Islands. The turquoise water surrounds the grey, shadowy rock structure forming the cave. The white waves crash against the rock to the left.